The Synthesis, Structure, and Electrical Characterization of (SnSe)1.2TiSe2. Issue 1 (27th November 2014) - Merrill, Devin R.; Moore, Daniel B.; Ditto, Jeffrey; Sutherland, Duncan R.; Falmbigl, Matthias; Winkler, Markus; Pernau, Hans‐Fridtjof; Johnson, David C.
Abstract: (SnSe)1.2 TiSe2 was found to self‐assemble from a precursor containing modulated layers of Sn–Se and Ti–Se over a surprisingly large range of layer thicknesses and compositions. The constituent lattices form an alternating layer superstructure with rotational disorder present between the layers. This compound was found to have the highest Seebeck coefficient measured for analogous TiX2 containing misfit layered compounds to date, suggesting potential for low‐temperature thermoelectric applications. Electrical characterization suggests that electrons transferred from SnSe to TiSe2 are responsible for the higher carrier concentration observed relative to bulk TiSe2 . The transfer of charge from one constituent to the other may provide a mechanism for doping layered dichalcogenides for various applications without negatively affecting carrier mobility. Abstract : The first intergrowth compound in the Sn–Ti–Se system was synthesized from modulated elemental reactants and was found to have a large negative Seebeck coefficient for 10 21 carriers. Electrical characterization suggests that charge transfer occurs between layers to stabilize the superstructure and provides conducting electrons to the TiSe2 layer.